A Compact Review of Industrial Robots: Dynamic Modeling, Control Strategies, and Operational Challenges - Kommey, Benjamin; Stephanie Essah; David Dery Kuusofaa; Samuel Boahene Jnr (Andalas Journal of Electrical and Electronic Engineering Technology, 2025)
When considering Industrial Robots, one often envisions large-scale mechanical systems integrated within manufacturing facilities, specifically designed to transport objects across assembly lines, perform complex assembly tasks, and handle material manipulation with high precision. These robots are capable of performing repetitive and demanding operations, but if proper safety protocols are not implemented, they can pose serious safety hazards to human workers. While these perceptions are accurate, they do not fully capture the complexity and extensive scope of industrial robotics. This review, supported by an exhaustive analysis of numerous technical reviews, academic papers, and research studies conducted over multiple years, synthesizes these findings to provide a comprehensive and sophisticated understanding of industrial robotics. It covers the intricacies of engineering design, including kinematic and dynamic modeling, as well as the development of advanced algorithms and control systems that enable precise, real-time operations. Additionally, it highlights the critical role these robots play in boosting productivity, ensuring operational efficiency, and maintaining consistency in manufacturing processes. With recent advancements in artificial intelligence, new perspectives have emerged regarding control and modeling strategies, paving the way for the development of cognitive robots capable of autonomous decision-making and adaptive behavior, thus opening exciting prospects for the future of industrial automation.